EFFECT OF ADDING WOOD POWDER ASH ON CBR VALUE IN STABILIZED HIGH PLASTICITY CLAY CEMENT AND LIME - Nugroho, Soewignjo Agus; Fatnanta, Ferry; Alridho, Muhammad Faizal (Universitas Ibn Khaldun Bogor, 2021)
Cement and lime are widely used as stabilizing agents for soft clays. Some pozzolanic materials have also been used as additives such as asphalt, geosta, fly ash (geopolymer), base ash, salt. Industrial waste such as rice husk ash, coal burning ash (geopolymer) is also used as an alternative for stabilization materials. This research aims to study the effect of sawdust ash, as wood waste, to replace cement and lime on the stabilization of high plasticity clay. The effectiveness of sawdust ash, in this study, was evaluated from the CBR value. The test samples were also reviewed under conditions with and without immersion and with and without curing. Based on the test results, lime is very effective as an additive because it increases the CBR value of more than 100 at a level of 10%. Wood husk ash also increases the CBR value by 100%. The use of cement, lime and wood husk ash requires curing time so that there is a strong bond between the clay and additives. The use of additives without curing did not increase the CBR value. In the stabilization of clay with 10% lime, replacement of lime with wood husk ash by 4%-6%, can be used as a road sub-grade with good quality.